The Relationship of Parenting Feeding Paterns to The Occurrence of Undernutrition in Children Under Five - Nurhamidah Octarya; Kurnia Dewiani; Linda Yusanti; Suriyati; Novianti; Linda Yulyani (The Indonesian Institute of Science and Technology Research, 2022)
Malnutrition can cause growth and development disorders and decreased concentration power. Poor food parenting is one of the factors causing malnutrition. This study aims to determine the relationship between eating parenting and malnutrition in children under five in Bengkulu City. This research design uses a cross-sectional approach. Further, the sample amounted to 53 respondents. The data sampling used a purposive sampling technique. Based on the results of univariate analysis of 53 respondents, there were 40 people (75.5%) who were <35 years old, 23 people (43.4%) who had a high school education, 30 people (56.6%) whose family income was 1.5 million, 37 people (69.8%) who do not work, 34 people (64.2%) who have a history of illness last six months, 49 people (92.5%) have a history of exclusive breastfeeding, 48 people (90.6%) who have a history of complete immunization, the majority of 35 people who have a poor diet (66.0%), the majority who have a Z-Score value is significantly less 34 people (64.2%). The results of the bivariate analysis test, which were reviewed statistically using Chi-Square analysis, showed a p-value = 0.741 > 0.05. It can be concluded that there is no significant relationship between parenting feeding patterns and the incidence of malnutrition in children under five with an OR value of 1.220, which means that mothers who have poor food parenting will be at risk of 1,220 times having toddlers with poor nutritional status.